Effects of forced deep breathing on blood flow velocity in the femoral vein: Developing a new physical prophylaxis for deep vein thrombosis in patients with plaster cast immobilization of the lower limb. Issue 162 (February 2018) - Nakanishi, Keisuke; Takahira, Naonobu; Sakamoto, Miki; Yamaoka-Tojo, Minako; Katagiri, Masato; Kitagawa, Jun
Abstract: Introduction: Patients with plaster cast immobilization of the lower limb have an estimated symptomatic venous thromboembolism rate of 5.5%. However, there is currently no practical physical prophylaxis for deep-vein thrombosis (DVT). The objective of this study was to examine the effects of forced deep breathing on peak blood velocity in the superficial femoral vein (PBVFV), which is a surrogate measure of the efficacy of thromboprophylaxis against DVT, in patients with plaster cast immobilization of the lower limb. Materials and methods: Nine young males and 18 elderly males were recruited. We immobilized the right lower limb of each subject with a plaster splint and measured PBVFV during forced deep breathing in supine and sitting positions. Results: In all subjects, PBVFV during forced deep breathing in both positions was significantly higher than at rest. There was no significant difference in the PBVFV change ratio for three breathing rates in the sitting position for the young subjects (15 breaths/min: 415%, 5 breaths/min: 475%, 3 breaths/min: 483%), whereas that for the elderly subjects at 3 breaths/min (449%) was significantly higher than that at 15 breaths/min (284%). Conclusions: Forced deep breathing significantly increased PBVFV in patients with plaster cast immobilization of the lower limb in both supine and sitting positions. Testing the efficacy and adherence in clinical contexts, and following up with the incidence rate of DVT in future studies, is necessary for the development of a new physical prophylaxis for DVT. Highlights: Forced deep breath increases venous blood velocity in healthy males with plaster cast. Peak blood velocity in the femoral vein is influenced by posture or pace of breaths. Change ratio of blood velocity resulted in at most a 4.8-fold increase at sitting.